2004
DOI: 10.1073/pnas.0307217101
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed carbocyclization of 1,6-enynes leading to six-membered rings or oxidized five-membered trifluoroacetates

Abstract: We describe palladium-catalyzed carbocyclization of 1,6-enynes leading to six-membered rings by water-originated hydride addition. Mechanistic features of this anomalous carbocyclization and isolation of a chiral five-membered C-Pd intermediate as an oxidized form of trifluoroacetate are also reported.T ransition metal-catalyzed carbocyclizations of 1,6-enynes A (1-4), such as cycloisomerization (5-11), metathesis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), skeletal reorganization (23-26), and ene reactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…( E )-1-Bromo-3-(3-(2-methyl-3-phenylallyloxy)prop-1-ynyl)benzene (2h): Following the same procedure as for the synthesis of 2f , in the presence of CuI (62 mg, 0.1 equiv) and PdCl 2 (PPh 3 ) 2 (115 mg, 0.05 equiv), 1-bromo-3-iodobenzene (0.53 mL, 1.3 equiv) in distilled diisopropylamine (6.8 mL), ( E )-(2-methyl-3-(prop-2-ynyloxy)prop-1-enyl)benzene [77] (611 mg, 1 equiv) was transformed to 2h (851 mg) in 76% yield. TLC (cyclohexane/ethyl acetate 90:10) R f 0.63; 1 H NMR (300 MHz, CDCl 3 ) δ 2.08 (d, J = 1.3 Hz, 3H), 4.31 (d, J = 0.8 Hz, 2H), 4.53 (s, 2H), 6.71 (d, J = 1.0 Hz, 1H), 7.30 (t, J = 7.8 Hz, 1H), 7.36–7.56 (m, 6H), 7.58 (dt, J = 8.0, 0.8 Hz, 1H), 7.75 (t, J = 1.6 Hz, 1H); 13 C NMR (75 MHz, CDCl 3 ) δ 16.0, 58.0 (2C), 85.1, 87.1, 122.5, 125.1, 127.0, 128.3, 128.5 (2C), 129.3 (2C), 130.1, 130.7, 132.0, 134.7, 134.9, 137.7.…”
Section: Methodsmentioning
confidence: 99%
“…( E )-1-Bromo-3-(3-(2-methyl-3-phenylallyloxy)prop-1-ynyl)benzene (2h): Following the same procedure as for the synthesis of 2f , in the presence of CuI (62 mg, 0.1 equiv) and PdCl 2 (PPh 3 ) 2 (115 mg, 0.05 equiv), 1-bromo-3-iodobenzene (0.53 mL, 1.3 equiv) in distilled diisopropylamine (6.8 mL), ( E )-(2-methyl-3-(prop-2-ynyloxy)prop-1-enyl)benzene [77] (611 mg, 1 equiv) was transformed to 2h (851 mg) in 76% yield. TLC (cyclohexane/ethyl acetate 90:10) R f 0.63; 1 H NMR (300 MHz, CDCl 3 ) δ 2.08 (d, J = 1.3 Hz, 3H), 4.31 (d, J = 0.8 Hz, 2H), 4.53 (s, 2H), 6.71 (d, J = 1.0 Hz, 1H), 7.30 (t, J = 7.8 Hz, 1H), 7.36–7.56 (m, 6H), 7.58 (dt, J = 8.0, 0.8 Hz, 1H), 7.75 (t, J = 1.6 Hz, 1H); 13 C NMR (75 MHz, CDCl 3 ) δ 16.0, 58.0 (2C), 85.1, 87.1, 122.5, 125.1, 127.0, 128.3, 128.5 (2C), 129.3 (2C), 130.1, 130.7, 132.0, 134.7, 134.9, 137.7.…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of a Pd 0 precursor, such as [Pd 2 (dba) 3 ], substrate 72 was converted into cyclohexadiene 73 in 69 % yield in benzene at reflux [Eq. (25)]. On the basis of the regioselectivity of the reaction, a mechanism relying on the oxidative dimerization of the triple bonds to form a palladacyclopentadiene intermediate of type 74 has been proposed.…”
Section: Palladium-catalyzed Polycyclization Sequences and Cyclodimermentioning
confidence: 99%
“…[25] For example, Hatano and Mikami described the synthesis of dihydropyran 35 from allylpropargyl ether 34 in the presence of a dicationic palladium/biphosphane system in DMSO as the solvent for 18 h at 100 8C [Eq. (13)].…”
Section: Reviewsmentioning
confidence: 99%
“…Studies with deuterium-labeled substrates revealed that the addition occurs in a trans fashion, thus the only suitable activation modes are either a pure alkyne activation or a dual activation by two metals. There is precedence on the formation of Pd-enolates and the coordination of Pd(II) to alkynes, however, based on previous studies, [71][72][73] the authors have ruled out the possibility that Pd(II) acts as soft-Lewis acids. Nonetheless, Balme and co-workers demonstrated that alkali metal enolates add to Pd(II)-activated alkynes.…”
Section: Enantioselective Conia-ene Reactionsmentioning
confidence: 99%